Aminomethylation of formononetin and cladrin by primary amines - Bondarenko, Svetlana; Frasinyuk, Mihaylo; Khilya, Volodimir (My University, 2009)
The reaction of natural isoflavones formononetin and cladrin with primary amines and formalin in the presence of a base catalyst was studied. Several novel substituted 9,10-dihydro-4H,8H-chromeno[8,7-e][1,3]oxazin-4-ones containing alkyl, benzyl, or heterylalkyl substituents in the N-9 position were synthesized.
Keywords: isoflavone; cladrin; formononetin; electrophilic substitution; ізофлавон; формононетин; кладрин; електрофільне заміщення; изофлавон; электрофильное замещение; кафедра харчової хімії